Determination of ejection coefficient of liquid-gas ejector with combined mixing chamber - Ponomarenko, Vitalii; Sliusenko, Andrii; Liulka, Dmytro; Yakobchuk, Roman (2023)
Introduction. The aim of the research was to develop a method for determining the actual ejection coefficient of a liquid-gas ejector with a combined mixing chamber. Theoretical calculation methods were used (balance equations of mass and energy in the form of the Bernoulli equation and the laws of hydrodynamics), experimental methods (ejection coefficients of an ejector with a combined mixing chamber were experimentally determined on a hydraulic bench in order to determine the experimental constant). The Sokolov-Zinger graph-analytical method was used to compare the ejection coefficients. Метою досліджень була розробка методики визначення фактичного коефіцієнта ежекції рідинно-газового ежектора з комбінованою камерою змішування. Використовували теоретичні методи розрахунку (рівняння балансу маси та енергії у формі рівняння Бернуллі та закони гідродинаміки), експериментальні методи (коефіцієнти ежекції ежектора з комбінованою камерою змішування експериментально визначали на гідравлічному стенді з метою визначення експериментальна константа). Для порівняння коефіцієнтів викиду використовували графоаналітичний метод Соколова-Зінгера.
Keywords: ejector; ejection; liquid-gas; mixing; ежектор; ежекція; рідина-газ; змішування; кафедра технологічного обладнання та комп’ютерних технологій проектування